Connections between sources of health and beauty information and indoor tanning behavior among college women. Issue 2 (17th February 2020) - Gall Myrick, Jessica; Noar, Seth M.; Sontag, Jennah M.; Kelley, Dannielle
Abstract: Objective: This study tested how media, family, and peer sources of health and beauty information predict indoor tanning (IT) beliefs and behavior. Participants: 210 undergraduate women at a state university in the southeastern United States. Methods: Respondents completed a survey about sources of health and beauty information, IT beliefs, and IT behavior. Correlations and a path model were used to test associations between variables. Results: Friends were positively and family were negatively associated with positive outcome expectations, with mood enhancement beliefs positively predicting behavior. Reliance on news positively predicted appearance damage and immediate risk, which both predicted behavior. Reliance on social media was negatively associated with beliefs about immediate risks. Conclusion: Health and beauty information from social media and from friends may promote beliefs about tanning, while information from news or one's family may reduce risky beliefs. Prevention efforts could leverage information sources to shift tanning beliefs and behavior.